Post-Mortem Analysis of Neuropathological Changes in Human Tinnitus - Faris Almasabi; Faisal Alosaimi; Minerva Corrales-Terrón; Anouk Wolters; Dario Strikwerda; Jasper V. Smit; Yasin Temel; Marcus L. F. Janssen; Ali Jahanshahi (Brain Sciences, 2022)
Tinnitus is the phantom perception of a sound, often accompanied by increased anxiety and depressive symptoms. Degenerative or inflammatory processes, as well as changes in monoaminergic systems, have been suggested as potential underlying mechanisms. Herein, we conducted the first post-mortem histopathological assessment to reveal detailed structural changes in tinnitus patients’ auditory and non-auditory brain regions. Tissue blocks containing the medial geniculate body (MGB), thalamic reticular nucleus (TRN), central part of the inferior colliculus (CIC), and dorsal and obscurus raphe nuclei (DRN and ROb) were obtained from tinnitus patients and matched controls. Cell density and size were assessed in Nissl-stained sections. Astrocytes and microglia were assessed using immunohistochemistry. The DRN was stained using antibodies raised against phenylalanine hydroxylase-8 (PH8) and tyrosine-hydroxylase (TH) to visualize serotonergic and dopaminergic cells, respectively. Cell density in the MGB and CIC of tinnitus patients was reduced, accompanied by a reduction in the number of astrocytes in the CIC only. Quantification of cell surface size did not reveal any significant difference in any of the investigated brain regions between groups. The number of PH8-positive cells was reduced in the DRN and ROb of tinnitus patients compared to controls, while the number of TH-positive cells remained unchanged in the DRN. These findings suggest that both neurodegenerative and inflammatory processes in the MGB and CIC underlie the neuropathology of tinnitus. Moreover, the reduced number of serotonergic cell bodies in tinnitus cases points toward a potential role of the raphe serotonergic system in tinnitus.